Faktor Pendukung Dan Penghambat Dalam Pembinaan Karakter Religius Ekstrakurikuler Forum Annisa - Wati, Dina Rahma; Rivauzi, Ahmad (An-Nuha, 2024)
Teenagers especially girls can be influenced by their social environment. Parents and educational institutions must speak up to help them become good Muslim women. Forum nnisa Syiar A women-only forum to develop Muslimah resources. SMK level annisa forum as an extracurricular activity. This study aims to explain the supporting and inhibiting factors in the implementation of religious character development through Forum Annisa extracurricular activities at SMKN 1 Batipuh. This research uses a qualitative method with a case study approach. Data collection techniques using interviews, observation and documentation methods. By using purposive sampling technique, the informants consisted of two Annisa forum supervisors and six female students. The interview results were analyzed through data collection, data reduction, presentation and conclusion drawing. The results showed that the supporting factor for Annisa forum extracurricular activities at SMKN 1 Batipuh was support from various parties. The inhibiting factor is the lack of awareness of female students, the lack of school support in terms of presenters, the duration of the Annisa forum time, and the lack of parental attention.